WOMEN'S COURAGE AS AN EFFECT OF A STRONG FRIENDSIDP BOND IN THURSDAYS AT EIGHT - Margaretha Alexandra Pribadi; Ekawati Marhenny Dukut (Soegijapranata Catholic University, 2011)
Having girlfriends may bring many advantages for women. They can relate and be comfortable with each other. This makes them talk about anything in a group. Thursdays at Eight talks about friendship bond and the power inside them through pain, rejection, ambition, and lost. This article, which uses Feminism approach, emphasizes in Third-wave Feminism and is intended to analyze thefriendship bond and the courage of the women in the novel. For example is how the characters in the novel get up and fight to reach what they want throughfriendship bond.